Complex impedance formalism: An alternative approach for exploration of relaxation dynamics in conductive materials. (15th November 2022) - Zulueta, Yohandys A.; Leyet, Y.; Guerrero, F.; Angada-Rivera, J.; Nguyen, Minh Tho; Pham-Ho, My-Phuong
Abstract: A new method, the complex impedance formalism, is presented to disclose the relaxation process of conducting materials. This method is an extrapolation of the dielectric modulus formalism in the Bode representation of the impedance. As in the dielectric modulus formalism, the relaxation process can be approached in both the frequency and time domains for non-Debye relaxation type. The complex impedance formalism is tested by analysis of the relaxation process of the solid BaTiO3 material at high temperatures. A combination of complex impedance and dielectric modulus formalism provides us with a better understanding concerning individual relaxation regions. The complex impedance formalism allows the hidden relaxation process at low frequency regime to be accessible, whereas the dielectric modulus formalism discloses the relaxation process at high frequency in mixed electronic-ionic conductors. Graphical abstract: Image 1 Highlights: A new formalism to disclose the relaxation process in mixed ionic-electronic material is presented. The relaxation process can be approached in both the frequency and time domains for non-Debye relaxation type. A combination of complex impedance and dielectric modulus formalism provides us with a better understanding concerning individual relaxation regions. The complex impedance formalism allows the hidden relaxation process at low frequency regime to be accessible, whereas the dielectric modulus formalism discloses the relaxation process at high frequency in mixed electronic-ionic conductors.